FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERUSAHAAN SEKTOR KONSUMEN PRIMER - Marvinico Lauren; Rosmita Rasyid (Jurnal Paradigma Akuntansi, 2026)
This research aims to obtain the results of the effect of leverage, sales growth, liquidity, and firm size on the financial performance of Consumer Non-Cyclicals Sector companies listed on the Indonesia Stock Exchange from 2019 to 2021. The method used in this research in sampling was purposive sampling. and obtained as many as 42 samples of companies. This research performs data processing using Eviews version 12 and WPS Office. The results of this research showed that leverage has a negative effect on financial performance, sales growth and firm size have a positive effect on financial performance, and liquidity has no effect on financial performance. The implication of this research is that a company's financial performance can be influenced by many factors, therefore companies need maximum consideration if they want to improve their financial performance.